2016
DOI: 10.1007/s00360-016-1009-x
|View full text |Cite
|
Sign up to set email alerts
|

The satiety factor oleoylethanolamide impacts hepatic lipid and glucose metabolism in goldfish

Abstract: Oleoylethanolamide (OEA) is an acylethanolamide synthesized mainly in the gastrointestinal tract with known effects in mammals on food intake and body mass through activation of peroxisome proliferator-activated receptor type α (PPARα). Since we previously demonstrated that acute treatment with OEA in goldfish resulted in decreased food intake and locomotor activity, as in mammals, we hypothesize that OEA would be involved in the control of energy metabolism in fish. Therefore, we assessed the effects of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Thus, PPARα is considered an output gene and shows daily rhythmic expression in a variety of tissues in mammals (Yang et al, 2006; Chen et al, 2010). This interaction between OEA and the circadian system has also been suggested in fish, since hepatic expression of bmal1a increases after OEA treatment in goldfish (Gómez-Boronat et al, 2016) and the expression of pparα is rhythmic in gilthead sea bream ( Sparus auratus ; Paredes et al, 2014) and zebrafish ( Danio rerio ; Paredes et al, 2015). Apart from these data, there is no evidence in fish on the possible daily rhythmicity in OEA and other NAEs.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Thus, PPARα is considered an output gene and shows daily rhythmic expression in a variety of tissues in mammals (Yang et al, 2006; Chen et al, 2010). This interaction between OEA and the circadian system has also been suggested in fish, since hepatic expression of bmal1a increases after OEA treatment in goldfish (Gómez-Boronat et al, 2016) and the expression of pparα is rhythmic in gilthead sea bream ( Sparus auratus ; Paredes et al, 2014) and zebrafish ( Danio rerio ; Paredes et al, 2015). Apart from these data, there is no evidence in fish on the possible daily rhythmicity in OEA and other NAEs.…”
Section: Introductionmentioning
confidence: 62%
“…In fact, it has been demonstrated in mammals that PPARα stimulates fatty acid oxidation and lipid catabolism (Charoensuksai and Xu, 2010; Chen and Yang, 2014; Liu et al, 2014). In addition, bmal1a is also rhythmic increasing after feeding, supporting its role as a lipogenic factor in mammals (Shimba et al, 2005, 2011; Zhang et al, 2014), and also in goldfish (Gómez-Boronat et al, 2016). Moreover, PPARα has been largely proposed as a link between lipid metabolism and circadian system in mammals (Yang et al, 2006; Chen and Yang, 2014; Ribas-Latre and Eckel-Mahan, 2016), in which circadian rhythms of PPARα are essential for the temporal coordination of genes involved in energy and metabolic process (Charoensuksai and Xu, 2010; Chen and Yang, 2014; Ribas-Latre and Eckel-Mahan, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…OEA plays a pivotal role in lipid metabolism by modulating lipids in circulation and tissues in addition to its satietogenic effect . Several experimental studies have shown the useful effects of OEA on lipid profiles (Supplemental Table 1) . Further investigations have indicated that the lipolytic activity of OEA and its effects on fatty acid mobilization by activating PPAR‐α and PPAR‐α target genes contribute to lipid metabolism .…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…Finally, some GI fatty acid ethanolamines, structural analogues of the endocannabinoids, as oleoylethanolamide (OEA) induces satiety in mammals (Fu et al 2003) and goldfish (Tinoco et al 2014b), where it is involved in the regulation of liver lipid and glucose metabolism (Gómez-Boronat et al 2016). In the rat, OEA modulates feeding by prolonging the time interval between meals rather than meal size (Gaetani et al 2003).…”
Section: Sort-term Signalling From Gitmentioning
confidence: 99%